2013
DOI: 10.1002/ejsp.1944
|View full text |Cite
|
Sign up to set email alerts
|

Upright and left out: Posture moderates the effects of social exclusion on mood and threats to basic needs

Abstract: Adopting a powerful posture leads individuals to feel more confident and dominant. Social exclusion can strongly impact individuals' mood and basic social needs. The current research combines these bodies of research, investigating the effects of dominant and submissive poses on responses to social exclusion and inclusion. In two experiments, participants held a slouching or upright pose and were either socially included or excluded using the Cyberball social exclusion manipulation. Social exclusion only affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…For example, when participants adopted UPs (instead of SPs) while receiving success feedback, they experienced more pride (Stepper & Strack, 1993). Similarly, Welker, Oberleitner, Cain, and Carré (2013) showed that for people in UPs, their mood was worse when they were socially excluded than when they were socially included, whereas no such effect was observed for people in SPs.…”
Section: Effects On the Actormentioning
confidence: 95%
“…For example, when participants adopted UPs (instead of SPs) while receiving success feedback, they experienced more pride (Stepper & Strack, 1993). Similarly, Welker, Oberleitner, Cain, and Carré (2013) showed that for people in UPs, their mood was worse when they were socially excluded than when they were socially included, whereas no such effect was observed for people in SPs.…”
Section: Effects On the Actormentioning
confidence: 95%
“…For instance, walking with an expansive posture may cause powerful feelings such as anger or pride but also negative affect such as sadness depending on the particular context (e.g., Cesario & McDonald, 2013). Indeed, studies have found that individuals adopting expansive postures report more negative mood when socially excluded (Welker et al, 2013) and higher depression scores when experiencing failure (Riskind, 1984). Accordingly, it has been proposed that the context may moderate the effects of displays on behavior (Cesario & McDonald, 2013).…”
Section: Outcome Assessmentmentioning
confidence: 99%
“…We term these expansive displays because the body is posed in a way that makes it appear taller and wider than when the body posture is neutral. The second set of motor displays covers withdrawal displays, including submissive (e.g., Welker, Oberleitner, Cain, & Carré, 2013), sad or fearful (e.g., Michalak et al, 2015;Shafir, Taylor, Atkinson, Langenecker, & Zubieta, 2013), closed (e.g., Latu et al, 2017), slouched (e.g., Ceunen, Zaman, Vlaeyen, Dankaerts, & Van Diest, 2014, and powerless displays (e.g., Bailey, LaFrance, & Dovidio, 2017). These displays we term contractive displays because the body is posed in a way that makes it appear shorter and smaller than when the body posture is neutral.…”
mentioning
confidence: 99%
“…A similar set of problems is also evident for the set of studies that were included in the p-curve analysis of EASE variables. That is, thirteen of sixteen studies reported a significant effect of postural manipulation on EASE variables but ten of these studies (described in Brinol, Petty, & Wegener, 2009;Kozak, Roberts & Patterson, 2014;Nair, Sagar, Sollers, Consedine, & Broadbent, 2015;Peper, Booiman, Lin, & Harvey, 2016;Riskind, 1983;Riskind, 1984;Teh et al, 2016;Veenstra, Schneider, & Koole., 2017 [Experiment 2], Welker, Oberleitner, Cain & Carre, 2013;Wilson & Peper, 2004) all failed to include either a control group or baseline measurements on the EASE variables. Only three of the thirteen studies were designed in a way that allows an inference to be drawn about the effect of power posing relative to a neutral posture on EASE variables.…”
Section: Emotion Affect and Self-evaluations (Ease)mentioning
confidence: 99%